A low cost kinect-based virtual rehabilitation system for inpatient rehabilitation of the upper limb in patients with subacute stroke: A randomized, double-blind, sham-controlled pilot trial. Issue 25 (June 2018) - Kim, Won-Seok; Cho, Sungmin; Park, Seo Hyun; Lee, Ji-Young; Kwon, SuYeon; Paik, Nam-Jong
Abstract: Background: We designed this study to prove the efficacy of the low-cost Kinect-based virtual rehabilitation (VR) system for upper limb recovery among patients with subacute stroke. Methods: A double-blind, randomized, sham-controlled trial was performed. A total of 23 subjects with subacute stroke (<3 months) were allocated to sham (n = 11) and real VR group (n = 12). Both groups participated in a daily 30-minute occupational therapy for upper limb recovery for 10 consecutive weekdays. Subjects received an additional daily 30-minute Kinect-based or sham VR. Assessment was performed before the VR, immediately and 1 month after the last session of VR. Fugl-Meyer Assessment (FMA) (primary outcome) and other secondary functional outcomes were measured. Accelerometers were used to measure hemiparetic upper limb movements during the therapy. Results: FMA immediately after last VR session was not different between the sham (46.8 ± 16.0) and the real VR group (49.4 ± 14.2) ( P = .937 in intention to treat analysis). Significant differences of total activity counts (TAC) were found in hemiparetic upper limb during the therapy between groups ( F 2, 26 = 4.43; P = .22). Real VR group (107, 926 ± 68, 874) showed significantly more TACs compared with the sham VR group (46, 686 ± 25, 814) but there was no statistical significance between real VR and control (64, 575 ± 27, 533). Conclusion: Low-cost Kinect-based upper limb rehabilitation system was not more efficacious compared with sham VR. However, the compliance in VR was good and VR system induced more arm motion than control and similar activity compared with the conventional therapy, which suggests its utility as an adjuvant additional therapy during inpatient stroke rehabilitation. Abstract : Supplemental Digital Content is available in the text